ANALISIS POLA ASUH ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA DI MASA PANDEMI - Hidayatulloh , Alpiana (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
This research aims to analyze parenting patterns on students' motivation in participating online learning during the pandemic. The subjects in this research were class X and XI IPA MA NW Kabar, totaling 15 students, taking the subject randomly. The research technique used in this research was interviews and questionnaires, then the results of interviews and questionnaires are analyzed descriptively. The results of the analysis of interview data are that there are four parenting patterns applied by parents, namely authoritarian parenting as much as 6.7%, democratic parenting as much as 26.7%, permissive parenting as much as 46.7% and neglect parenting as much as 20%. The percentage of students' motivation in participating in online learning is influenced by the parenting pattern applied as much as 65% is in the sufficient category.